The odd quantum - Treiman, Sam B. (Princeton University Press, 1999)
"This is a concise but comprehensive account of quantum mechanics written by a respected physicist for popular science readers. Sam Treiman makes quantum mechanics accessible to nonspecialists, combining mastery of the material with clear, elegant prose and infectious enthusiasm as he conveys the substance, methods, and profound oddities of the field."--Jacket